Strategi Pimpinan Pondok Pesantren Tahfidz Qur’an Insan Madani Dalam Meningkatkan Kualitas Santri - Inom Nasution; Ahmad Ardhi Mauluddin Sitorus; Hasian Rambe; Lydia Amelia; Nindi Aulia Putri; Rizhani Masrura; Yusril Ardiansyah; Zahara Ahmad Fauzi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The main problem in this study is how the leadership strategy of the Tahfidz Qur'an Islamic Boarding School Insan Madani in improving the quality of students. The purpose of this study was to determine the leadership's efforts in improving the quality of the students of the Tahfidz Qur'an Insan Madani Islamic Boarding School. This type of research uses qualitative methods in descriptive form. The source of this research data was obtained in two ways, namely the first primary data source, namely the main data that the researcher obtained directly in the form of direct information from the leadership of the cottage and the second secondary data source, namely the data obtained indirectly through literature studies such as books, thesis journals and websites. internet related to the title of the researcher. The results showed that the leadership strategy of the Tahfidz Qur'an Islamic Boarding School Insan Madani in improving the quality of students. This can be seen from the efforts of the leaders of the Insan Madani Islamic Boarding School by improving the quality of students in the process of implementing the daily program of santriawan and female students. The efforts to improve the quality of students carried out by the leadership of the Insan Madani Islamic Boarding School in improving the quality of students are: (1) Programs for deepening reading of the Qur'an, (2) strengthening educational programs to strengthen the character of students, (3) implementing daily activity programs namely as a supporter of the formation of the quality of students.